Antioxidant and antibacterial activities of Bika (Ampelocissus martini Planch.) seed oil - Angot, Rose Imee Lynn Navarro (2016.)
Ampelocissus martini Planch., locally known as Bika, is a native tropical plant generally found in Southeast Asia. It is abundant in Panay Island, particularly in the provinces of Antique and Iloilo. Despite that the fruit is being consumed as food, used as medicine and made into wine, very few scientific studies pertaining to Bika grape exist. Hence, this study focused on its antioxidant and antibacterial activities. The antioxidant activities were carried out through the % DPPH radical scavenging activity and reducing power method. Results show that the Bika seed oil has antioxidant activity. Its IC50 using DPPH assay is 23.63 ppm. Moreover, it also showed a significant antioxidant activity based on the results from the reducing power assay. Both results demonstrated that Bika grape seed oil has antioxidant activity. On the other hand, the mean zones of inhibition using disk diffusion assay was used to assess the antibacterial activity of Bika seed oil against Escherichia coli and Staphylococcus aureus. Only the antibiotic Gentamicin showed active antibacterial property whereas the Bika seed oil showed little zone of inhibition, only goes to show that it has an inactive antibacterial property.
Thesis -- Bachelor of Science in Chemistry. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Bika (Ampelocissus martini Planch); DPPH -- method; Disk diffusion method; Antioxidant -- Bika; Antibacterial -- Bika